Age decreases quality of life in adolescents with intractable epilepsy - Prastiya Indra Gunawan; Theresa Laura Limanto; Darto Suharso (Universa Medicina, 2015)
BackgroundIntractable epilepsy considerably affects both the private and social life of the patient. The objective of this study was to determine the quality of life of intractable epileptic adolescents and its correlated factors. Methods A cross sectional study was conducted in the Pediatric Neurology outpatient clinic of Dr. Soetomo Hospital. All intractable epileptic adolescents aged between 10 to 16 years were asked to complete a questionnaire on quality of life in epilepsy for adolescents (QOLIE-AD-48). A multiple linear regression was used to analyze the data through SPSS v17.0.ResultsThirty one patients with mean age of 12.41 ± 1.40 years were enrolled in the study. The mean duration of diagnosed intractable epilepsy was 6.12 ± 4.30 years. Mean score for impact of epilepsy was 57.11 ± 24.50, for memory and concentration 53.54 ± 26.66, physical functioning 65.56 ± 23.67, social stigma 52.23 ± 17.48, social support 52.64 ± 22.69, behavior at school 57.51 ± 26.50, attitude 53.40 ± 16.70 and health perception 61.51 ± 11.30. Multiple linear regression results showed that quality of life (QOL) was not significantly correlated with duration of epilepsy, sex and nutritional status (p>0.05), but increasing age was significantly decreases quality of life (p<0.05). ConclusionsIntractable epileptic adolescents have higher scores for physical functioning and health perception, but lower scores for social stigmatization. Social support has extremely low scores. Increasing age decreases quality of life in adolescents with intractable epilepsy.